Practicality of Implementing Sub-Clause 8.4 [Advance Warning] of the FIDIC 2017 Red Book in Egypt - Ibrahim, Gehad (AUC Knowledge Fountain, 2025)
Disputes in construction projects can cause cost and time overruns that can be detrimental to the parties involved and to the project. Several measures have been advocated by the industry’s practitioners in an attempt to avoid disputes and their adverse impacts. One of these measures is the introduction of advance warning sub-clauses in construction contracts, where the contracting parties play a proactive and collaborative role in warning each other of potential adverse impacts to the project. Such clauses have been in the NEC suite of standard construction contracts for decades and have recently found their way to the 2017 edition of the FIDIC Red Book. In light of the consistent popularity of the FIDIC contract in the Egyptian construction industry for nearly three decades, this study explores the practicality of implementing this sub-clause, 8.4 [Advance Warning], in the Egyptian construction market and touches on whether applying this sub-clause could prove to be a legal requirement under Egyptian law. Interviews were conducted with practitioners in the industry to explore the extent of the market’s willingness to adhere to the obligations set forth in sub-clause 8.4. Twenty professionals with more than ten years of experience in project and contract management in the Egyptian market were interviewed and the study found that interviewees would not give an advance warning in 65% of cases that require the same. This percentage increases to 78.5% when an underlying commercial benefit was added to each scenario. Challenges to implementation were also identified through the interviews and categorized into the following: 1: Pursuit of Commercial Benefit 2: Assuming No Obligation to Inform Other Party 3: Engineers' Reluctance to Inform Contractors Without Consulting Employers 4: Reluctance to Give Warnings for Events that did not Materialize 5: Concern that Contractors May Seeks Monies Via Other Claims The original sub-clause was then amended to take these challenges into account. Afterwards, the redrafted sub-clause and the research findings were presented to experts within the industry who possess fifteen or more years of experience to validate the results. The experts had further insights and suggested further tweaks to the amended sub-clause to reach a final revised version. It is notable that this final version’s employment is not limited to the 2017 FIDIC Red Book but can be employed in any edition of the FIDIC suite of contracts and in any standard form of contracts by including it in the pertaining particular conditions. This research topic was also the subject of a webinar conducted by the Chartered Institute of Arbitrators that was attended by over forty professionals who also had insights about this topic. The professionals’ opinions are also shared in this paper.